Implementation of sequential design based water level monitoring and controlling system - Hussain Attia; Beza Getu; Abdullah Asaad; Ahmed Abbas; Mahmoud Al Nuaimi; Abdulhadi Brazi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In currently decades, water usage either for domestic or commercial purposes is facing critical conditions which negatively affects the sustainability of our environment. From this point of view, reducing water consumptions will participate in the solution of water saving. Monitoring and controlling the tank water level are important functions which effect and work on reduction of water consumption.  Many studies in literature focus on proposing a high performance water level monitoring and controlling systems based on either computerized units or microcontroller units. However these systems are characterized by complexity and high cost. In this paper, a highly flexible implemented electronic system is introduced based on sequential design by using general purpose discrete components. The proposed system present simple design of water level sensing stage, in addition, this paper showing full design, simulation, and implementation steps of an automation system which is able to control switching the state of the water pump in accordance to the current level of water in the tank.